Service learning : can our students learn how to become a successful student? - Mikelić, Nives (Array, 2006)
The goal of this paper is to discuss the origin of the higher education (HE) issues in Croatia and to introduce service learning methodology into our faculties. Service learning (SL) is a form of education where learning occurs when students apply what they learn to community problems and reflect upon their experience as they seek to achieve real objectives for the community. Service learning as a teaching methodology can be easily integrated with ICT in order to achieve better learning and teaching outcomes. Finally, we present the results of two surveys conducted with Croatian students in order to reveal their issues and concerns and we offer solutions learned from our experiences in US.